Evaluation of almond flower tolerance to frosts by chlorophyll fluorescence - Kodad O.; Socias i Company R.; Morales F. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
Most almond cultivars are susceptible to negative temperatures, a limiting factor for almond expansion to regions with risks of spring frosts. Flower and fruitlet tolerance to frosts has only been studied so far by observing the morphological damages produced by low temperatures. Thus, our objective was the evaluation of chlorophyll fluorescence (CF) to estimate the tolerance of 12 commercial almond cultivars of different origin to low temperatures. Flowers were maintained for 24 hours at different temperatures (0º, -1º, -2º and -3ºC), after which CF was measured. In general, the variable fluorescence (Fv) and the ratio Fv/Fm decreased with time in all genotypes, although the rate of decrease depended on the genotype. The decrease of these parameters was slower in the cultivars tolerant to low temperatures, whereas the decrease was linear or/and sigmoid in the susceptible cultivars. In general, the classification of genotypes with this technique according to their frost tolerance level agreed with the published references. These results point out that chlorophyll fluorescence is a promising technique (fast, quantitative, easy and non-destructive) to ascertain the tolerance of almond genotypes to frosts independently of their blooming time.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)